Runggu or local wisdom-based conflict resolution: The role of the Pengituai Kuta - Toba Sastrawan Manik; Suharno Suharno (Faculty of Social and Political Science, Universitas Airlangga, 2020)
Conflict resolution is needed by society, especially in Indonesia, which has a diverse culture; it is inherent in the culture. Conflict resolution based on local wisdom is needed to create peace in society because it always strives to produce decisions that are win-win solutions. This research examines the importance and role of local wisdom as a form of conflict resolution in society and examines the role of the Pengituai Kuta in Pakpak culture as a conflict resolution method. This research is qualitative research with a case study approach conducted in Matanari Hamlet, Ujung Teran Village, Dairi Regency, North Sumatra. The data collection techniques used were semi-structured interviews, observation, and literature study. The subject of information in this study consisted of three people, namely one member of Pengituai Kuta Matanari (JM) and the Head of Matanari Hamlet (PP), and Cultural Practitioner or Humanist Pakpak (LB). According to Miles and Huberman’s model, the data is processed, which includes the collection, reduction, presentation, and conclusion. This finding shows that the Pengituai Kuta has an essential and influential role in resolving horizontal conflicts in Matanari Hamlet. The local wisdom of the Indonesian people already has conflict resolution systems and methods. In Pakpak culture, Pengituai Kuta refers to representatives of community leaders who are considered experienced and exemplary. Every conflict is resolved by deliberation-consensus (runggu) in an open, egalitarian, and full of brotherhood.